2020
DOI: 10.1371/journal.pone.0244729
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of three home fall hazard assessment tools for older adults in Thailand

Abstract: This study aimed to examine the predictive validity of two internationally well-known instruments, the Modified Home Falls and Accidents Screening Tool (Modified HOME FAST) and the Modified Home Falls and Accidents Screening Tool-Self Report (Modified HOME FAST-SR), and the newly developed Thai Home Falls Hazard Assessment Tool (Thai-HFHAT) (69 items) in predicting falls among older Thai adults. It also aimed to examine the predictive validity of the two abbreviated versions (44 and 27 items) of the Thai-HFHAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…11 There was a report of psychometric properties of 44-question Thai-HFHAT as the adjusted hazards ratio (HR) was 1.26 (95% CI: 1.20-1.33), a cut-off was 18 points, the sensitivity and specificity were 0.93 and 0.72, and the area under the receiver operating characteristic curve (AuROC) was 0.90. 12 In addition, the study also found that the 44-question Thai-HFHAT requires only 30 minutes for elderly users to complete all the questions. Occasionally, due to the inability to answer all the elders' questions in practice, the remaining questions were answered by a caregiver or a village health volunteer for the elders.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…11 There was a report of psychometric properties of 44-question Thai-HFHAT as the adjusted hazards ratio (HR) was 1.26 (95% CI: 1.20-1.33), a cut-off was 18 points, the sensitivity and specificity were 0.93 and 0.72, and the area under the receiver operating characteristic curve (AuROC) was 0.90. 12 In addition, the study also found that the 44-question Thai-HFHAT requires only 30 minutes for elderly users to complete all the questions. Occasionally, due to the inability to answer all the elders' questions in practice, the remaining questions were answered by a caregiver or a village health volunteer for the elders.…”
Section: Introductionmentioning
confidence: 86%
“…The inter-rater reliability of the 44-question version was higher than the Modified HOME FAST-SR (Thai version) (ICC = 0.64). 12 This is probably because the Thai-HFHAT was designed to have questions listed in an organized manner with drawings to help illustrate each room in a house, allowing subjects to identify home hazards at ease. However, the text in the HOME FAST-SR may have been confusing.…”
Section: Personal Characteristics Associated With Home Hazardsmentioning
confidence: 99%
“…It has been designed in such a way that the elderly can fill it out with or without help from Thai village health volunteers (VHV). The ICC of inter-rater reliability and test-retest reliability for the Thai-HFHAT was 0.87 (95% CI: 0.78-0.93) and 0.78 (95% CI: 0.58-0.89), respectively [9]. The cutoff point of the Thai-HFHAT was 18, which predicted the risk of falls due to home hazards in the elderly.…”
Section: Introductionmentioning
confidence: 89%
“…The survey method examined the achievement of fall risk screening data of 450 elderly [9] who were recruited to participate and fulfill the sample size conducted in phase I. Because the suitable samples were from 200 or more, the study used a confirmatory factor analysis (CFA) [10].…”
Section: Phase Imentioning
confidence: 99%
“…Thus, there is a need to select and validate a high-quality self-reporting screening tool to assess home hazards that can be utilized for the stroke population and their caregivers. The use of home hazards instruments sensitive to cultural settings may capture more valuable and meaningful hazards (168,169). With home hazards, healthcare professionals should focus on clutter, assistive devices (i.e., mobility aids, shoe), and the functional aspects of the person-environment fit, and in particular, attention should be given to the bathroom and stairs area as these were also found to be related to falls (170,171).…”
Section: Under-recognizing the Importance Of Environmental Factors Asmentioning
confidence: 99%